1990
DOI: 10.1007/bf00300776
|View full text |Cite
|
Sign up to set email alerts
|

Secretory immunoglobulin A and inhibitory activity of bacterial adherence to epithelial cells in urine from patients with urinary tract infections

Abstract: To assess the role of local immune response against bacterial invasion of the urinary tract we studied 168 patients with bacteriuria. Urinary secretory immunoglobulins A (sIgA) were measured using radial immunodiffusion or enzyme-linked immunosorbent assay (ELISA). In particular, ELISA is a very suitable assay for measuring the low levels of sIgA in urine. Furthermore, we used a quantitative in vitro adherence assay to investigate the attachment of Escherichia coli to human uroepithelial cells after incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…UPEC infection elicits Ab responses in animal models and humans. Both IgG and secretory IgA have been found in urine and act as neutralizing Abs (32)(33)(34). A variety of vaccine candidates has been tested in both animal models and humans with the purpose of evoking protective humoral responses (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…UPEC infection elicits Ab responses in animal models and humans. Both IgG and secretory IgA have been found in urine and act as neutralizing Abs (32)(33)(34). A variety of vaccine candidates has been tested in both animal models and humans with the purpose of evoking protective humoral responses (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…UPEC-specific antibodies are detected in the urine of infected patients (202) and in the urine or serum of animals exposed to UPEC antigens (116,217,260,264). Urinary IgG and IgA from UTI patients are capable of inhibiting UPEC adherence (58,249,263). Patient studies have also suggested that antibody responses to pyelonephritis are, in general, stronger and last longer than humoral responses to cystitis (80,134,135).…”
Section: Covert Operations: Cellular and Humoral Adaptive Immune Respmentioning
confidence: 99%
“…It is increasingly accepted that salivary IgA might play a minor role in saliva-mediated aggregation of bacteria [14]. In histological examinations, Stephens and his colleagues [15] found that immunoglobulin was rarely associated with meningococci on the mucosal surface.…”
Section: Discussionmentioning
confidence: 99%